Las organizaciones culturales y su relación con las redes sociales virtuales. Caso: Arena y Esteras - Saldaña Manche, Walter Vladimir (2020)
The present research work has as main axis to know the Cultural Association Arena and Mats and how they have evolved over time. It also seeks to discover the influence that virtual social networks have, especially the Facebook account, in the growth of its institution. In order to understand this case, an exploration has been made of the main concepts of organization, organizational culture, virtual social networks and the Internet. Subsequently, we proceed to review the events that marked the beginning of the organization, the various difficulties they had to overcome and the recognition they obtained for their work in favor of community. Then an investigation is carried out on the main concepts of virtual social networks and the Internet, in addition, an analysis is made of the messages that are published, especially in the Facebook account of Arena and Esteras. Finally, the conclusions are presented in an orderly and detailed manner, mentioning the various improvements that should be made both at the organizational level and at the communication level.